(untitled) (Academicia Globe: Inderscience Research, 2023)
The idea that infection is a process completely dependent on the microorganism dominates the minds of doctors. The same major disorders in the body’s immune system that precede it, i.e. immunodeficiencies are ignored. Hence the main therapeutic doctrine - to destroy the microorganism by any means, which causes the emergence of increasingly resistant variants, and attempts to “sterilize” the macroorganism induce dysbiosis and chronic forms of immunopathology.